Innovative Photonic Sensors for Safety and Security, Part III: Environment, Agriculture and Soil Monitoring - Giovanni Breglio; Romeo Bernini; Gaia Maria Berruti; Francesco Antonio Bruno; Salvatore Buontempo; Stefania Campopiano; Ester Catalano; Marco Consales; Agnese Coscetta; Antonello Cutolo; Maria Alessandra Cutolo; Pasquale Di Palma; et al. (Sensors, 2023)
In order to complete this set of three companion papers, in this last, we focus our attention on environmental monitoring by taking advantage of photonic technologies. After reporting on some configurations useful for high precision agriculture, we explore the problems connected with soil water content measurement and landslide early warning. Then, we concentrate on a new generation of seismic sensors useful in both terrestrial and under water contests. Finally, we discuss a number of optical fiber sensors for use in radiation environments.